Z rozważań nad wyodrębnieniem i metodologią prawa socjalnego - Sierpowska, Iwona (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
Social law is identified in Poland as a field of didactics and scholarly research. In addition, attempts have also been made at recognizing social law as a separate academic discipline. Such a classification is justified by the specific scope of the subject matter, social considerations, and practical requirements. Despite its connection to labor law and social security law, social law displays many characteristics particular to public law, especially administrative law. For this reason the role the state plays in social and legal studies cannot be overlooked. This role is exhibited in the shaping of social policy, the fulfillment of social functions, and the protection of social security – through which social law becomes a plane of interdisciplinary scholarly activity. In terms of research methodology, the discipline discussed employs methods specific to administrative law and social security, while simultaneously seeking out its own research identity. Developing a method constructed around social support that may serve as one of social law’s distinctive features could serve as an inspiration.
Keywords: prawo socjalne; świadczenia nieodpłatne; metodologia; dyscyplina naukowa